Effect of Freeze-Drying, Spray-Drying, and Foam-Mat-Drying Encapsulation Techniques on Vitamin C Level in Fruit Powder: A Scoping Review - Baruroh, Durotul; Suselo, Yuliana Heri; Kusumawati, Ratna; Dono Indarto (Media Publikasi Cendekia Indonesia, 2025)
Vitamin C is an essential micronutrient with important antioxidant and physiological roles. However, it is highly unstable during processing due to its sensitivity to heat, oxygen, and light. This scoping review mapped evidence on drying-based encapsulation techniques: freeze drying, spray drying, and foam-mat drying. It examines their effect on the vitamin C level in fruit powder. A systematic search was conducted in PubMed, ScienceDirect, Springer, MDPI, and Google Scholar for studies published between 2015 and 2025. The search followed the PRISMA-ScR framework. Seven studies met the criteria and covered acerola, camu-camu, banana, açaí, papaya, satsuma mandarin, orange peel, and mulberry. The findings show that freeze-drying was consistently the most effective technique for retaining vitamin C levels. Some studies even reported an increase in vitamin C levels, possibly due to the breakdown of the fruit matrix, which made the nutrient more available. During Spray drying, low retention values (11%) were obtained in banana paste, and almost total retention (99%) was achieved in camu-camu pulp. The retention of mulberry juice during optimized foam-mat drying amounted to a maximum level of 90%. Coating materials, such as gum Arabic (GA) and carboxymethyl cellulose (CMC), provided better stability in vitamin C levels. However, there are some gaps regarding encapsulation efficiency, degradation kinetics, and particular mechanisms of the matrix that could clarify retention rates beyond 100%. Thus, future studies should focus on these parameters for the refinement of scalable yet low-cost drying strategies of functional fruit powders.